INTEGRATION OF TECHNICAL AND ECONOMIC TRAINING IN THE FORMATION OF PROFESSIONAL COMPETENCIES OF FUTURE ROAD TRANSPORT SPECIALISTS - Prystinskyi S. М.; Maksymova, O. S.; Maksymov, S. V. (Systems and Technologies, 2026)
The article addresses the problem of integrating technical and economic training in the formation of professional competencies of future automotive transport specialists under conditions of digitalization, development of transport logistics, and increasing requirements for economically justified decision-making. Based on the analysis of recent scientific studies, it has been established that existing educational approaches mostly implement technical and economic components separately, which reduces the effectiveness of forming integrated competencies required for professional activity in the transport sector. An integrated competency-based training model is proposed, grounded in the concept of a multidimensional educational space and taking into account the synergistic interaction of academic disciplines. The model provides a formalized representation of compe- tency formation through a system of weighting coefficients and interdisciplinary interaction parameters, enabling the assessment of the level of integration within an educational program. Transport logistics is identified as a key integrative component that ensures the connection between technical knowledge and economic reasoning in the process of professional decision-making. A quantitative approach to evaluating training effectiveness is introduced based on an integral indicator reflecting the levels of technical, economic, and integrated competencies. The practical significance of the proposed model lies in its applicability for optimizing curricula, improving training quality, and aligning educational outcomes with the needs of the modern transport services market. The results obtained can be applied in the design and modernization of educational programs for automotive transport specialists.